Exploring Initial Public Offerings (IPOs) investment strategies in Malaysia - Murugasu, Thangarajah @ M.Thiyagarajan (2014)
In Malaysia, IPO offering price setting is still lack of transparency and remains puzzling to investors. Investors are left with many unanswered questions. Investors have no idea on the fair value of the IPO firms and whether the IPOs are really undervalued and to what extent. Successful IPO subscribers are neither guided on whether they should take the capital gain on the first trading day nor remain holding the shares. For unsuccessful IPO subscribers, they do not know whether it is still profitable to purchase the IPOs on or after the First-Day of listing on the secondary market. All these questions can be answered to some extent if the fair value of the IPO firm can be estimated. The aim of this study is to develop an investment strategy for IPO investors to make various investment decisions such as whether to subscribe for IPOs, to buy, sell, or hold the shares on the secondary market. To further aid the investors especially retail investors this study has developed investment algorithm. The investment algorithm will be useful to make various investment decisions such as whether to subscribe for IPOs, buy, sell, or hold on first-Day, first-Week and first-Month closing price. Two techniques, Multiple Linear Regression (MLR) and Comparable Firm Approach (CFA), were employed to arrive at a close enough estimation of IPO firms’ fair values from 1995 to 2008. The first-day, first-week, and first-month closing prices for the newly listed IPO firms were also estimated based on the MLR techniques only.